Revision and Sinicization of William Milne’s Two Friends - SU, Jiayi (Journal of Research for Christianity in China (JRCC), 2026)
Two Friends is the first dialogue-based chapter novel serialized by Protestant missionary William Milne (1785–1822) in the Chinese Monthly Magazine between 1817 and 1819. It embodies both religious propagation and literary experimentation. As a quintessential text of Sino-Western cultural encounter in the 19th century, its revised editions underwent dozens of reprints over nearly a century, spanning regions including Fuzhou, Shanghai, Ningbo, and Beijing. This paper presents a detailed examination of the textual variations of Two Friends over the past century. By analyzing the sinicized translation strategies employed in its revisions, this study explores the diverse pathways of Sinicization during the Protestant dissemination in China.